Chlorpyrifos induces neuronal cell death via both oxidative stress and Akt activation downstream-regulated CHOP-triggered apoptotic pathways. (February 2023) - Lin, Jhe-Wei; Fu, Shih-Chang; Liu, Jui-Ming; Liu, Shing-Hwa; Lee, Kuan-I; Fang, Kai-Min; Hsu, Ren-Jun; Huang, Chun-Fa; Liu, Kun-Min; Chang, Kai-Chih; Su, Chin-Chuan; Chen, Ya-Wen
Abstract: Chlorpyrifos (CPF) is one of the most abundant and widely used organophosphate pesticides for agricultural, industrial, and household purposes in the world. Epidemiological studies have reported that CPF can induce neurotoxic impairments in mammalian, which is linked to an important risk factor for development of neurodegenerative diseases (NDs). However, limited information is available on CPF-induced neurotoxicity, with the underlying exact mechanism remains unclear. In this study, CPF exposure (10–400 μM) significantly reduced Neuro-2a cell viability and induced apoptotic events, including the increase in caspase-3 activity, apoptotic cell population, and cleavage of caspase-3/−7 and PARP. Exposure of Neuro-2a cells to CPF also triggered CHOP activation. Transfection with CHOP-specific siRNA markedly suppressed the expression of CHOP, and attenuated cytotoxicity and apoptotic events in CPF-exposed Neuro-2a cells. Furthermore, CPF exposure obviously evoked the phosphorylation of Akt as well as ROS generation in a time-dependent manner. Pretreatment with LY294002 (an Akt inhibitor) effectively attenuated the CPF-induced Akt phosphorylation, CHOP activation, and apoptotic events, but not that ROS production. Of note, buffering the ROS generation with antioxidant N -acetylcysteine effectively prevented the CPF-induced ROS generation, CHOP activation, and apoptotic events, but not that the Akt phosphorylation. Collectively, these findings indicate that CPF exposure exerts neuronal cytotoxicity via the independent pathways of ROS generation and Akt activation downstream-regulated CHOP-triggered apoptosis, ultimately leading to neuronal cell death. Highlights: Chlorpyrifos (CPF) induced neuronal cell cytotoxicity and death underwent apoptosis. Akt-activated CHOP signaling was involved in CPF-induced neuronal apoptosis. Oxidative stress was also involved in CPF-induced neuronal cell apoptosis. Oxidative stress and Akt signals were independent in CPF-induced neuronal apoptosis.